Multitasking and Network-building: China’s Party Diplomacy in Latin America - Zhang, Xinyu (Ibero-América Studies, 2024)
This paper examines China’s Party diplomacy and its practice in Latin America. As part of China’s overall diplomatic strategy, the CPC’s diplomacy in the region aims to fulfill multiple tasks. Using publicly available documentation, this paper creates a dataset covering exchanges between the Communist Party of China (CPC) and Latin America to analyze the CPC’s network-building in the region since 2013. The results show that to achieve China’s strategic goals, the CPC’s contacts in Latin America are characterized by diversification and openness. Daily interactions and knowledge exchanges are the main content of the CPC’s interactions with its contacts. Additionally, global, regional, and bilateral exchange mechanisms, especially the cooperation mechanism between the CPC and Latin American leftists, have been established. Although the party-based approach to Sino-Latin American relations faces challenges from political volatility, ideological differences, regional fragmentation, and external intervention, China’s party diplomacy in the region still has great opportunities for development. Inter-party exchanges not only help us understand the development of Sino-Latin American relations but also provide an important perspective for studying cooperation among Third World countries.